Studi Filsafat Pendidikan Perenialisme sebagai Upaya Membentuk Karakter Kristiani - Leonardo, Noldy Ferry; Henri Sirangki (Institut Agama Kristen Negeri Manado, 2024)
The educational philosophy of perennialism is a philosophy that focuses on eternal universal values and truths which of course have a significant impact on character formation. Seeing the crisis in the world of education today, especially regarding the character and morals of students, the step taken is to direct the principles of education to the principles of the past which are called perennialism. The aim of this research is to discuss the importance of perennialism education as an effort to shape Christian character so that life reflects it more and more every day. the character of Jesus Christ. The research method used is qualitative with data collection techniques through literature reviews. The collected data is then analyzed through four channels, namely data reduction, presentation, data verification and interpretation. The research results show that the perennialist educational philosophy has a significant role in shaping Christian character. This approach emphasizes universal truths and eternal moral values in society, as well as developing character by referring to universal truths. On the other hand, Christian education places greater emphasis on character formation based on God's absolute truth, with a foundation of truth found in the Bible. Then, perennialist education not only shapes character, but also contributes to the development of a complete and potential individual by using education from the past, namely the 5th century BC (Plato and Aristotle) to the Middle Ages (Thomas Aquinas). For further research related to this topic, the author recommends this article as a reference in further research.